The Use of Live Streaming Technologies in Surgery: A Review of the Literature. Issue 1 (January 2022) - Abu-Rmaileh, Muhammad; Osborn, Tamara; Gonzalez, Santiago R.; Yuen, James C.
Abstract : Background: Live streaming surgery is a developing communication platform in medicine. To maximize the technological advances that allow for the live streaming of surgery, it is crucial to have an understanding of the various video-capturing devices that are available and their pros and cons of implementation. Possible barriers to the widespread use of live streaming surgery include cost, concerns about patient safety and privacy, and limited understanding of the current available resources. In this article, we present the results of our literature review of techniques for live streaming of surgery as a means to inform readers and promote their implementation. Methods: We conducted a literature review of the literature to identify previous articles indexed in PubMed and Ovid. We used the following search terms: [Surgery AND Streaming], which generated 32 articles for initial review. References were reviewed within each document to find similar articles that were not captured by the initial search. The article selection criteria were peer-reviewed publications, case reports, and case series describing the use of live surgical streaming technologies. Results: Literature review showed enhanced surgeon interaction with viewers and improved anatomy scores with the widespread use of live streaming. Surgeons reported positive feedback and wished to engage in more sessions in the future. The largest barriers to implementation of streaming technology are video quality through the Internet and patient information protection. Conclusions: Live streaming of surgery for educational purposes has not been widely accepted in surgical training programs to date. Streaming accessibility has advanced over the past 2 decades with the availability of handheld mobile devices. However, little has been done to allow for live streaming of surgery to trainees in a manner compliant with the Health Portability Insurance and Accountability Act.